دور الابتكار التسويقي في تحسين صورة العلامة التجارية للمؤسسة الاقتصادية الجزائرية - دراسة حالة مؤسسة كوندور Condor- الجزائر - بعلي, حمزة; بن خليفة, أحمد (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة لمعرفة دور الابتكار التسويقي في تحسين صورة العلامة التجارية للمؤسسة الاقتصادية الجزائرية، وذلك من خلال معرفة أثر الابتكار في مجالات المزيج التسويقي الاربعة (المنتج، السعر، الترويج، التوزيع) على تحسين صورة العلامة التجارية، وتم اسقاط الدراسة النظرية على مؤسسة كوندور (Condor) الجزائر، وتم اتباع المنهج الوصفي التحليلي في الدراسة، ولتحقيق الهدف قمنا بتوزيع (98) استمارة، وتم اختبار الفرضيات باستخدام أسلوب الانحدار (Regression)، وتوصلت الدراسة لمجموعة من النتائج أهمها وجود أثر إيجابي وعلاقة موجبة بين جميع المجالات التسويقية (المنتج، التسعير، الترويج، التوزيع) وتحسين صورة العلامة التجارية للمؤسسة محل الدراسة، وأوصت الدراسة بضرورة تنمية روح الابتكار لدى الأفراد العاملين، كما يجب التركيز على نشاط البحث والتطوير الذي يساهم في وضع إدارة متعلقة بابتكار الأفكار التسويقية. This study aimed to find out the role of innovation marketing in improving the brand image of the Algerian economic institution, by identifying the impact of innovation in the four marketing mix areas (product, price, promotion, distribution) on improving image of the brand, , the study was dropped at corporation CONDOR Algeria, the analytical descriptive approach was followed in the study, , to achieve we distributed (98) form on the selected sample, , the hypotheses were tested using the simple regression method, the study reached a number of results, the most important of which is the existence of positive impact and positive relationship between all independent variables in improving the brand image superiority of the institution under study, the study recommended the need to develop the spirit of innovation among working individuals, Emphasis should also be placed on research and development that contributes to the management of marketing innovation ideas.
Keywords: الابتكار ; المزيج التسويقي ; صورة العلامة التجارية ; الابتكار التسويقي